Analysis of the Effect of Climate Change Literacy on Climate Awareness of Students in MAN 1 Yogyakarta, Yogyakarta City - Nurhalimah, Nafisa; Susilawati, Siti Azizah (Universitas Muhammadiyah Surakarta, 2023)
Objective: This study aims to investigate the influence of Climate Change Literacy on Climate Awareness among students at MAN 1 Yogyakarta. Methodology: This research method is quantitative method, the research design used is simple linear regression test. The population of this study were all grade X students at MAN 1 Yogyakarta, totaling 170 students. The respondent sample was determined by sampling technique or saturated sample. The variables of this study are Climate Change Literacy and Climate Awareness variables. Climate Change Literacy variables include understanding, impacts, and causes of climate change, while Climate Awareness includes attitude, personal concern, knowledge, and awareness includes attitude, knowledge, personal concern, multiplicative action, and climate-friendly behavior. Data collection techniques were carried out by observation and questionnaires. Results: The results showed that the level of Climate Change Literacy at MAN 1 Yogyakarta was dominated by the high category, which was 51% with an average value of 78 which was in the range of 70-89. The level of Climate Awareness of students at MAN 1 Yogyakarta is also dominated by the high category, which is 65% with a high average of 71. The simple linear regression test conducted also obtained positive results. Climate Change Literacy can affect the Climate Awareness of students at MAN 1 Yogyakarta by 5.8%. Application/Originality/Value: Thus, this study concludes that there is an influence between Climate Change Literacy on Climate Awareness at MAN 1 Yogyakarta.